Academic Interest Scale for Adolescents: Development, Validation, and Measurement Invariance With Chinese Students - Luo, Zheng; Dang, Yun; Xu, Wenjie (Frontiers in Psychology, 2019)
Hidi and Renninger’s four-phase interest development model was identified as the most complete and widely used theoretical model illustrating the essence of academic interest. Using the model along with current research literature as a basis, this study aimed to develop and initially validate a generic multidimensional instrument to measure academic interest across different school subjects in the Chinese education context; this instrument was called the Academic Interest Scale for Adolescents (AISA). Three large samples of Chinese junior high school students were recruited by cluster sampling in the study. (1) Sample 1(N = 552; 45.5% girls; 12.31 [SD = 0.98] years, range = 10-15 years) completed the draft of AISA, Intrinsic Motivation Scale and Scale for Adolescents’ Flow State in Learning in math and English. (2) Sample 2 (a subgroup of Sample 1, 411 students) completed the AISA in math and English again two months later after the first survey. (3) Sample 3 (N = 1,780; 50.1% girls; 13.69 [SD = 0.97] years, range = 12-16 years) completed the AISA in math, English and Chinese. Identically worded items were used in AISA, except for the name of the subject. An exploratory factor analysis for math in sample 1 using principle axis factoring and promax rotation resulted in a 29-item AISA containing four dimensions: emotion, value, knowledge, and engagement, and the latent variables together explained 59.40% of the total variance. Confirmatory factor analysis for math, English and Chinese in sample 3 suggested the four-factor model fits well in different samples and subjects. Scale scores showed adequate internal consistency (the Cronbach's α for AISA and each subscale ranged from .86 to .93) and acceptable test-criterion relationships (correlations between the AISA score and intrinsic motivation and flow state in learning > .51, ps < .001). Furthermore, the structural measure invariance across subjects, time (two-month interval), genders and grades were upheld. The AISA promises to be a useful tool for the evaluation of academic interest among Chinese adolescents and can be administered in different educational settings, i.e., different subjects, time, genders and grades.